Biological Integrity of Azorean Native Forests Is Better Measured in Cold Season - Tsafack, Noelline (2023)
ABSTRACT: The Azorean archipelago, recognized as one of the world’s biodiversity hotspots, is home to a diverse and unique community of arthropod species, highlighting a notable degree of endemism. However, the native forests that support these species are facing signiﬁcant degradation due to habitat loss and fragmentation. In this study, we aimed to determine the ideal season for measuring the biological integrity of forest sites using a biological integrity index (IBI) based on arthropod communities captured with Sea, Land, and Air Malaise (SLAM) traps. Drawing on more than thirty years of research experience in the Azorean forests, we selected twelve reference sites, six representing preserved native forest and six representing disturbed native forest, and compared how IBI values vary between seasons. IBI values exhibited consistent variations between seasons in disturbed sites, indicating that measuring the biological integrity in these areas can be conducted at any time of the year without a speciﬁc seasonal preference. In contrast, signiﬁcant differences were observed in pristine forest sites, with the winter season and the combination of winter and spring data (cold semester) showing notably higher values compared to other seasons and semesters. This ﬁnding suggests that measuring the biological integrity of preserved sites is best optimized in the cold seasons, while the detection of exotic species impact is most effective in summer and autumn. Consequently, if resources are limited, monitoring efforts should be concentrated in the winter and summer seasons to obtain the maximum and minimum values of IBI, respectively. Additionally, our study suggests that the summer season is the optimal time to detect potentially invasive exotic species.